Reconstructing English Curriculum under the MBKM Policy to Foster Intercultural Communicative Competence: Effectiveness, Challenges, and Opportunities - Andi Anugrah Surya Ardhy; Fadhlan Saini; Nurjayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the effectiveness of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in developing intercultural communication (ICC) competencies among students of English language education. This area currently lacks empirical evidence in the Indonesian higher education context. Using a mixed-methods design with a sequential explanatory model, quantitative data were collected through a Likert-scale questionnaire based on Kirkpatrick’s four-level evaluation model and Byram’s ICC framework, and further expanded upon through semi-structured interviews. The study involved 82 questionnaire respondents and five interview participants, selected using purposive sampling to capture the diverse experiences of students who had participated in MBKM for at least one semester. Findings indicate that 82.9% of students found the learning methods easy to understand, and 67% rated the material as relevant to their academic needs, reflecting positive outcomes at Kirkpatrick’s Levels 1 through 4. Students also reported increased cultural awareness and opportunities for authentic interactions, aligning with the five ICC dimensions in Byram’s model. However, challenges persist, including gaps in interdisciplinary understanding, heavy workloads, and inconsistent support from lecturers. These results suggest that MBKM has the potential to be a transformative platform for developing linguistic, cultural, and collaborative skills, provided that curriculum coordination and pedagogical reinforcement for lecturers are systematically implemented. Practical implications include structured study load management, standardized feedback mechanisms, and intercultural pedagogy training for lecturers. Limitations include its single-semester scope, limited participant diversity, and reliance on self-reported data, highlighting the need for multi-institutional longitudinal research that combines perception-based and performance-based measures.